Seasonal Forecast Information Synthesis and Dissemination in Association with CRAFT Tanzania and AICCRA - ESA - Keizer, Menno; Kabuka, Godfrey; Demissie, Teferi Dejene (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
The Netherlands Development Organization (SNV) in partnership with the CGIAR Research Program on Climate Change, Agriculture, and Food Security (CCAFS) for East Africa, Wageningen University & Research (WUR), Agriterra and Rabo Bank is implementing the Climate Resilient Agribusiness for Tomorrow (CRAFT) project in Eastern Africa (Kenya, Uganda and Tanzania) funded by the foreign ministry of the Netherlands. The CRAFT program uses an inclusive business development approach to support the international and Dutch efforts on climate change and sustainable production in arable farming. The program works with and through the private sector. It supports public sector partners in creating an institutional environment for wide-scale adoption of climate-smart agricultural (CSA) practices, including more efficient use of water and (renewable) energy sources. Here we present a regional capacity building workshop report on ‘Seasonal Forecast Information Synthesis and Dissemination.’ Jointly organized by the Accelerating Impacts of CGIAR Climate Research for Africa program for Eastern and Southern Africa (AICCRA-ESA) and ICPAC together with SNV in Tanzania with the following objectives: (i) To create seasonal forecasting awareness and disseminate seasonal forecasts for the upcoming growing season, (ii) Introducing the current state of sub-seasonal and seasonal forecasting and enhancing experts’ capacities in using the monthly and seasonal climate forecasting tools for the agricultural sector as shared by TMA and ICPAC. The workshop drew several public and private professional (e.g., experts from TMS, NARES, MoA, insurance, finance, and private sector value chain actors) in climate, climate change, and weather forecasts from various national and international (e.g., SNV, Agriterra and Rabo Bank etc.) organizations. 37 participants took part – of which 17 were women and 7 were youths. The general setup of the workshop was short presentations, plenary discussions, and breakaway groups to discuss specific topics in greater detail.